Racial Disparities in Use of Chiropractic Services by Medicare Beneficiaries Aged 65 to 99 in Los Angeles County, California. (April 2016) - Whedon, James M.; Kimura, Melissa N.; Phillips, Reed B.
Racial and ethnic disparities in utilization of chiropractic services have been described at the state level, but little is known about such local disparities. We analyzed Medicare data for the year 2008 to evaluate by ZIP code for utilization of chiropractic services among older adults in Los Angeles County, California. We evaluated for availability and use of chiropractic services by racial/ethnic category, quantified geographic variations by coefficient of variation, and mapped utilization by selected racial/ethnic categories. Among 7502 beneficiaries who used chiropractic services, 72% were white, 12% Asian, 1% black, 1% Hispanic, and 14% other/unknown. Variation in the number of beneficiaries per ZIP code who used chiropractic services was highest among Hispanics, blacks, and Asians. We found evidence of racial disparities in use of chiropractic services at the local level in Los Angeles County. Older blacks and Hispanics in Los Angeles County may be underserved with regard to chiropractic care.